Development and Validation of a Technique for Casting Anatomical Features and Toolmarks1. Issue 6 (21st September 2016) - Aland, Rachel Claire; Piper, Alan; Gosden, Edward
Abstract: Time may elapse between examination of marks inflicted on the body and comparison with a potential weapon. Two‐dimensional photographs may be inadequate for effective comparison of a three‐dimensional mark with a putative instrument. Taking a cast and producing a positive image results in a lasting three‐dimensional record. This project aimed to develop and demonstrate the accuracy of an easy technique for production of long‐lasting positive images (using plaster of Paris and dental alginate). Casts of facial features of embalmed cadavers were used to produce a positive image of the face (death mask). Measurements of distances between facial anatomical landmarks were compared with measurements of distances between the same landmarks on the death masks to assess accuracy of reproduction. There were no significant differences between cadaver and death mask in 6 of 9 measurements, indicating this technique has high accuracy with less mobile facial features, but produces deformation of pliable features.